The Cobalamin-Dependent Gene Cluster of Listeria monocytogenes: Implications for Virulence, Stress Response, and Food Safety - Anast, Justin M.; Bobik, Thomas A.; Schmitz-Esser, Stephan (Frontiers in Microbiology, 2020)
Several genes of the eut, pdu, and cob/cbi operons are responsible for the metabolism of ethanolamine (EA) and 1,2-propanediol (PD) and are essential during the pathogenic lifecycles of various enteric pathogens. Studies concerning EA and PD metabolism have primarily focused on bacterial genera from the family Enterobacteriaceae, especially the genus Salmonella. Listeria monocytogenes is a member of the Firmicutes phylum and is the causative agent of the rare but highly fatal foodborne disease listeriosis. The eut, pdu, and cob/cbi operons are organized as a single large locus collectively referred to as the cobalamin-dependent gene cluster (CDGC). The CDGC is well conserved in L. monocytogenes; however, functional characterization of the genes in this cluster and how they may contribute to Listeria virulence and stress tolerance in food production environments is highly limited. Previous work suggests that the degradation pathway of PD is essential for L. monocytogenes establishment in the gastrointestinal tract. In contrast, EA metabolism may be more important during intracellular replication. Other studies indicate that the CDGC is utilized when L. monocytogenes is exposed to food and food production relevant stress conditions. Perhaps most noteworthy, L. monocytogenes exhibits attenuated growth at cold temperatures when a key EA utilization pathway gene was deleted. This review aims to summarize the current knowledge of these pathways in L. monocytogenes and their significance in virulence and stress tolerance, especially considering recent developments.